Evaluasi In Vivo Biokompatibilitas Implan Hidrogel Hidrokoloid Alami Untuk Aplikasi Biomedis - Humayra , Sitiya; Sabira, Anisa; Sonia, Gina; Salman, Salman; Yulia, Rahma (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Hydrogels are promising biomaterials for biomedical applications due to their high biocompatibility, three-dimensional structure resembling biological tissue, and their ability to gradually degrade within the body. Notably, hydrocolloid hydrogels based on natural polymers, such as porang-sago glucomannan, demonstrate significant potential for applications like drug delivery systems and tissue engineering. The biocompatibility of these materials is crucial to ensure they are well accepted by body tissues without causing adverse reactions. Therefore, this study aims to evaluate the in vivo biocompatibility of hydrocolloid hydrogel implants made from crosslinked porang-sago glucomannan using citric acid, with a focus on biomedical applications. The method used in this study involved the implantation of hydrogel implants in male mice weighing approximately 25 grams, divided into four groups: three groups with different hydrogel implant formulations and one control group without implants. After 10–20 days post-implantation, the tissue surrounding the implant was evaluated through histopathological analysis using Hematoxylin-Eosin (H&E) staining. The results showed that the hydrogel implants exhibited good biocompatibility, with a mild inflammatory response predominantly characterized by macrophages and moderate fibrotic capsule formation. No pathological signs such as necrosis or granulomas were observed in the tissue surrounding the implant. Formulations F1 and F5 demonstrated better biocompatibility profiles compared to F3, showing lower inflammatory responses. In conclusion, hydrocolloid hydrogel implants based on porang-sago glucomannan exhibit good biocompatibility potential for subcutaneous and skeletal muscle applications. However, further optimization is required to improve tissue integration and minimize the gap between the implant and surrounding tissue. This study provides a foundation for the further development of hydrocolloid hydrogels as biomaterials for biomedical applications, such as drug delivery systems and tissue engineering.